Reproductive biology and pollination mechanisms of Epidendrum secundum (Orchidaceae). Floral variation: a consequence of natural hybridization? - Pansarin, Emerson Ricardo [UNESP]; Amaral, Maria do Carmo Estanislau do (Blackwell Publishing, 2008)
The phenology, flower morphology, pollination mechanism and reproductive biology of Epidendrum secundum were studied in a semi-deciduous forest at the Serra do Japi (SJ), and in the Atlantic rain forest of Picinguaba, both natural reserves in the State of Sao Paulo, southeastern Brazil. E. secundum flowers all year round, with a flowering peak between September and January. This species is either a lithophytic or terrestrial herb in the SJ, whereas, in Picinguaba, it grows mainly in disturbed areas along roadsides. E. secundum is pollinated by several species of diurnal Lepidoptera at both study sites. In Picinguaba, where E. secundum is sympatric with E. fulgens and both share the same pollinators, pollen transference between these two species was recorded. E. secundum is self-compatible but pollinator-dependent. It is inter-compatible with E. fulgens, producing fertile seeds. In contrast to the population of the SJ, in the Picinguaba region, floral morphology is quite variable among plants and some individuals present flowers with characteristics in-between both sympatric species, suggesting that natural hybridization occasionally occurs. The anthropogenic perturbation is probably the cause of the occurrence of E. secundum in the Picinguaba region, enabling its contact with E. fulgens.
Keywords: Epidendroideae; Epidendrum; Laeliinae; Orchidaceae; pollination; reproductive biology